GASTRO-INTESTINAL COMPLICATIONS POST OPEN HEART SURGERY-NONOCCLUSIVE MESENTERIC ISCHEMIA - Konstantin Dimitrov; Hristo Stoev; Gencho Nachev (Peytchinski Publishing, 2020)
Purpose:Nonocclusive mesenteric ischemia (NOMI) is rare but often lethal complication after cardiac surgery. The use of vasopressors, age, implantation of intra-aortic balloon pump, the duration of cardio-pulmonary bypass are the main risk factors described in the literature. The purposes of this study are to be represented the most typical prognostic factors and clinical manifestations of NOMI, condition which is not so effortlessly diagnosed. Methods:The study was designed as a retrospective study of all patients who underwent cardiac surgery in our institution from October 2002 to December 31, 2017. Data from clinical trials worldwide was also used for the preparation of this study. Results:9298 patients were operated in our institution for the period 2002-2017. 114 (1.2%) developed abdominal complications after cardiac surgery. In 17 (0.2%), explorative laparotomy with bowel resection for nonocclusive mesenteric ischemia was performed.Nonocclusive mesenteric ischemia (NOMI) is rare but often lethal complication. The progression of NOMI is associated with poor prognosis for the patients. Despite the surgical exploration and necrotic bowel resection, the mortality rate in these patients is dramatically high (over 80%). Conclusion:Diagnosis and treatment of non-occlusive mesenteric ischemia (nomi) remain challenging in modern clinical practice, requiring accurate and punctual evaluation of all patients with predisposing factors for development of this dramatic and often fatal condition.